Dill—Anethum graveolens L. - James M. Stephens (EDIS, 2003)
This document provides an overview of dill (Anethum graveolens L.), detailing its botanical characteristics, cultivation practices suitable for Florida, and common culinary uses. It highlights the plant’s adaptability to various soils, preferred planting times, and recommended varieties such as 'Long Island Mammoth'. Additionally, it describes harvesting methods and the use of dill in flavoring pickles, meats, and sauces. Original publication date May 1994.